Mister Shivers: The Doll in the Hall and Other Scary Stories - Brallier, Max; Rubegni, Letizia (New York : Scholastic Inc., 2021)
The Clark children are Mia's first babysitting job, and everything is going fine until she sees a life-sized doll sitting in the hallway; a doll that was not there before, a doll that Mr. Clark knows nothing about, and whose eyes follow Mia-- and that is only one of the five scary stories with unexpected twists that are included in this collection.
The doll in the hall -- The cast -- Bright white teeth -- The Jack-o-lantern -- Billy smiled.
Keywords: Dolls -- Juvenile fiction; Horror tales; Children's stories, American; Dolls -- Fiction; Horror stories; Short stories; Childern Horror fiction; Short stories